2021
DOI: 10.1007/s10489-021-02616-8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional analysis and data-driven forecasting of confirmed COVID-19 cases

Abstract: The coronavirus disease 2019 (COVID-19) is rapidly becoming one of the leading causes for mortality worldwide. Various models have been built in previous works to study the spread characteristics and trends of the COVID-19 pandemic. Nevertheless, due to the limited information and data source, the understanding of the spread and impact of the COVID-19 pandemic is still restricted. Therefore, within this paper not only daily historical time-series data of COVID-19 have been taken into account during the modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Based on the RNN and attention mechanism, 35 Qin 36 proposed a dual-stage attention-based recurrent neural network (DA-RNN), which demonstrated great success in temporal forecasting, it seems the fitness of this model regarding the features of water quality is matched but it needs deeper research. Jing 37 combined historical time-series data of COVID-19 with geographic and local factors in the DA-RNN model to predict COVID-19 cases, the model has better performance than support-vector-regression and the encoder-decoder network on the experimental datasets. Huang 38 exactly forecasts wind power generation by historical power and wind speed information in DA-RNN.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the RNN and attention mechanism, 35 Qin 36 proposed a dual-stage attention-based recurrent neural network (DA-RNN), which demonstrated great success in temporal forecasting, it seems the fitness of this model regarding the features of water quality is matched but it needs deeper research. Jing 37 combined historical time-series data of COVID-19 with geographic and local factors in the DA-RNN model to predict COVID-19 cases, the model has better performance than support-vector-regression and the encoder-decoder network on the experimental datasets. Huang 38 exactly forecasts wind power generation by historical power and wind speed information in DA-RNN.…”
Section: Introductionmentioning
confidence: 99%
“…Another study [83]) analyzed the spread of COVID-19 in the most affected Brazilian cities using hybrid and single ARIMA models, which integrated EEMD and ARIMA techniques. The results showed that the EEMD performed approximately 27% better than the single model [33,[47][48][49][53][54][55]71,74,106,[110][111][112][134][135][136][137][138][139][140][141][142][143].…”
Section: Plos Onementioning
confidence: 99%
“…The attention approaches are inspired by human attention visual mechanisms, which use limited attention to quickly screen high value information from a large amount of information. This not only contributes to increase the prediction performance but is also efficient in gaining insight into information that is more critical to the model outputs instead of learning non-useful information [37,127,128].…”
Section: Non-intrinsically Interpretable Modelsmentioning
confidence: 99%
“…The rest of the papers, e.g., [98,127,132], mostly utilize the data of one country or region, especially from the US. The analyzed studies focus on different research objectives.…”
Section: Literature Analysis Of Epidemiological Ai Researchmentioning
confidence: 99%